For a Sociology of Art: Dancing Cyborgs Between Digital Choreographies and Speculative Horizons - De Feo, Linda (Italian Sociological Review, 2024)
Human creativity records and throws again the dynamics of social transformations. It expresses itself into poetics that must be costantly interpreted. These poetics exhort to think of the complex relationship between narrative fields, techno-communicative mutations and epistemological frontiers. The paper will focus on the analysis of the mirroring between the creative parable traced by contemporary digital choreographies and the speculative horizon. Object of the reflection will be some significant segments of imaginary, conceivable as transpositions into choreutical acts of theoretical assumptions. These theories can be intended as narrations of the present and of the future, particularly careful in the interpretation of the structural processes. It will attempt to demonstrate how by the actual acceleration of the computational power in the area of the simulation and in the area of the perceptual reorientation, the intersection between the spectacular domain and the conceptual one produces an extension of the operative sphere of the dance. Like many forms of narrative, the terpsichorean art is increasingly acquiring a heuristic valence. The dancers destined to inhabit the mathematized space of digital descriptions incarnate the connection between the political experience - meaning the latter term in its etymological significance - and the sociomorphic representation of the human body. The protagonists of the works examined represent on aesthetic level the sense-informational métissage realized by the process of cybernatization of the human being, reflect the suspension of the semantic duality between biology and technique, interpret therefore the chimerical reconfiguration of the statute of contemporary identities.